A Pharmaceutical Study of an Ayurvedic Formulation- Vachadi Churna - K Sai Manikanta; Ch. Sri Durga; G. Lavanya (AYUSHDHARA, 2025)
Vachadi Churna is a herbo-mineral formulation mentioned in the classical text called Susruta Samhitha for the management of Yuvana pidaka. It contains Vacha, Lodhra, Saindhava Lavana and Sarshapa as ingredients. Vachadi Churna is in Churna form (powder) which should be mixed with water and applied on the affected area. The pharmaceutical procedures adopted in this preparation are Churna nirmana and Lepa. In the present study, Churna of Vacha, Lodhra, Saindhava Lavana and Sarshapa were taken in a Khalwa yantra and homogenously mixed to prepare Vachadi Churna. The procedures were conducted step by step in accordance with classical references and established Standard Operating Procedures (SOPs). Process loss and total yield were carefully recorded. Pharmacological action of the Vachadi Churna is discussed in brief.